Ciona pomponiae Monniot & Monniot 1989 - Sanamyan, Karen; Sanamyan, Nadya (Zenodo, 2007)
Ciona pomponiae Monniot & Monniot, 1989 (Figure 1) Ciona pomponiae Monniot and Monniot, 1989: 17. Ciona gefesti Sanamyan, 1998: 98. Material examined: RV Keldish , cruise 22, st. 2328, 1814– 1920m, 53°26.59'N, 160°21.00'E – 53°25.76'N, 160°21.40'E, 14 August 1990, one specimen. Previous records: E Pacific, Galapagos Islands (Monniot and Monniot 1989); Bering Sea (Sanamyan, 1998). Description. The laterally flattened specimen is 30mm high and 12mm wide. The test is firm (in alcohol) and translucent and colourless. Several thick branched root-like processes of the test are on both sides of the posterior end of the body. It was not possible to determine how the specimen was attached, although it appears to have been attached by more than its posterior end. The body was detached from the test in preservative. Both apertures are on short obscurely lobed siphons (number of lobes cannot be counted). The branchial siphon is terminal and the atrial is in the middle of the dorsal mid-line of the body. Longitudinal muscle ribbons continue from the siphons to the posterior end of the body. On each side, three of these originate on the branchial siphon and two on the atrial. The dorsal ribbon of the branchial siphon and ventral ribbon of the atrial siphon fuse together in the middle of the body to form one muscle, so four evenly spaced longitudinal ribbons are on each side of the posterior half of the body. Transverse (circular) body muscles are thin, numerous, but well spaced, not forming a continuous layer. On the siphons they more crowded and thicker, forming definite sphincters. About 30 long curved branchial tentacles are attached to the margin of a high muscular velum. The prepharyngeal band is composed of an unusually high anterior and a low posterior lamella and is not indented dorsally. A small C-shaped dorsal tubercle is just anterior to a rather large ganglion. The neural gland is small, on the right side of the ganglion. The flat branchial sac lacks any plications. Regularly spaced lamellar transverse vessels ...